Maximum power point tracking (MPPT) in solar panels - Vera, Jhon Edwin; Bayona, Jhon Fredy; Sanchez Cayanza, Ricardo (Visión electrónica, 2014)
When it comes to alternative energy, solar panels are one of the most studied due to its excellent performance under uniform solar radiation. This paper shows the advantages, simulation and implementation algorithm developed in an incremental conductance lowend DSP -digital signal processing- Texas Instrument TMS320F28069 R , in order to find and extract maximum power, performing tests on a resistive load.